Structural, thermal, mechanical and rheological properties of polylactic acid/epoxidized soybean oil/organoclay blends - Ali, Fathilah; Anuar, Hazleen; Jamaluddin, Jamarosliza (Elsevier, 2018)
Plastics are manufactured from non-degradable polymers such as polystyrene, polyethylene and many more, in which their light weight and long-lasting property are causing terrible environmental pollution. To overcome the problem, researchers are exploring on biodegradable materials that can substitute conventional polymers. Among the biodegradable polymers, polylactic acid (PLA) is a biodegradable aliphatic polyester derived from lactic acid, which can be obtained from the fermentation of starchy materials (Mehta et al., 2006). In spite of many attractive properties of PLA, such as biodegradability, high strength and modulus, PLA shows lower flexibility and higher cost, thus limiting the applications of PLA (Rasal et al., 2010). Epoxidized soybean oil (ESO) is an epoxidized derivative of a mixture of esters of glycerol with various saturated and unsaturated fatty acids. In previous study, ESO has been used as a plasticizer in PLA with 38% increase in elongation at break with 20 parts per hundred (phr) ESO loading (Ali et al., 2009). However, the tensile strength, yield stress and modulus of PLA decreased with addition of plasticizer. It has been reported that addition of plasticizer generally increases the elongation at break but decreases the strength and modulus. Thus, one method that can be used to improve the properties of polymer matrix is by incorporating fillers such as clay (Pluta et al., 2006a; Najafi et al., 2013). Incorporation of clay into PLA exhibited improvement in water vapor barrier and antimicrobial properties (Rhim et al., 2009; Castro-Aguirre et al., 2018). There are two methods that can be used to disperse the clay in polymer matrices: solution blend and meld blend. In the solution blend method, solvent is used in large amount to dissolve the polymers thus, improving the intercalation of polymer chains and clay platelets (Ozdemir et al., 2016). Whereas, for melt blend method, the layered silicate is mixed with the polymer matrix at the melting temperature of the polymer. This method is mostly used as it is more environmental friendly and polymers can be melt processed. It has been reported that the PLA/​clay nanocomposites were prepared by melt blending of PLA with sepiolite and halloysite clays (Russo et al., 2014). The addition of oligo(є-caprolactone) as compatibilizer has improved the dispersion of silicate layers in nanocomposites (Ray et al., 2002). Enhancement of properties such as crystallization rate (Pluta et al., 2006b), tensile, impact strength, modulus (Najafi et al., 2015), gas permeability, water barrier property (Şengül et al., 2017) and biodegradability (Castro-Aguirre et al., 2018) were observed in PLA/​clay nanocomposites. Dispersion of clay is very crucial in obtaining homogeneously dispersed filler in polymer matrix, in which, dispersion of clay in PLA matrix using electric effect was reported by Geun et al. (2016). Thus, this study aimed to prepare PLA blend using ESO as a plasticizer and Cloisite 30B as an organoclay. The PLA/​ESO/​organoclay nanocomposites were melt mixed with different ratios of organoclay and then investigated the structural, thermal, mechanical and rheological properties of the nanocomposites.